Algeria : Financial System Stability Assessment, including Reports on the Observance of Standards and Codes on the following topics; Monetary and Financial Policy Transparency and Banking Supervision. (IMF Staff Country Reports; Country Report ;, 2004)
Algeria's Financial System Stability Assessment highlights the Observance of Standards and Codes on monetary and financial policy transparency and banking supervision. Financial intermediation in Algeria will be bank-based in the future, and only politically difficult decisions to gradually sell state banks will eliminate the drag that current banking practices have on resource allocation. No system dominated by state banks has avoided large loan losses or contributed effectively to economic development.